FINANCIAL COMPETITION OF COUNTRIES AND TRANSFORMATION OF TAX STRATEGIES IN CONDITIONS OF GLOBAL UNCERTAINTY AND HYBRID CHALLENGES (INNOVATIVE ECONOMY, 2025)
Bukovskyi M.M., Mykhaylyak Y.Z.  FINANCIAL COMPETITION OF COUNTRIES AND TRANSFORMATION OF TAX STRATEGIES IN CONDITIONS OF GLOBAL UNCERTAINTY AND HYBRID CHALLENGESPurpose. The aim of the article is to substantiate the transformation of tax strategies aimed at maintaining economic activity and financial competitiveness of countries in a global environment characterized by a high level of uncertainty and the presence of hybrid challenges.Methodology of research. The methodological basis of the study is created by a set of general scientific and special approaches that allowed for a systematic study of financial and tax competition in the context of global uncertainty and hybrid challenges. The following methods are used in the work: theoretical generalization – to substantiate the content of the concepts of “financial competition” and “tax strategy”; systemic approach – to determine the relationship between global challenges, economic security and tax strategies of the state; statistical, analysis and synthesis – to assess the main changes in tax systems; comparative analysis – to compare tax models of different countries; abstract and logical method – to generalize the directions of transformation of tax strategies in the context of global uncertainty, and to formulate conclusions. Findings. It is substantiated that the global polycrisis caused by energy, financial, technological and security shocks have strengthened the role of fiscal policy in ensuring the stability of states. It is established that financial competition is multi-level in nature; therefore, it often intersects with tax competition in practice, because under the influence of hybrid challenges, countries can be attractive for investment through improving tax systems, introducing incentives, increasing transparency and harmonizing fiscal norms. The state of global economic uncertainty and its impact on financial competition are assessed. Trends in corporate taxation in the world that contribute to the formation of fairer tax architecture are analysed. The features of the formation of Ukraine's tax strategy are clarified, including from the beginning of 2022. The parameters of the transformation of tax strategies are substantiated, in particular, adaptability, sustainability, digitalization, environmental orientation, social justice, etc.Originality. The substantiation for the transformation of tax strategies implemented at the global, regional and national levels has been further developed. This transformation is due to the need to take into account fiscal sustainability, institutional capacity and security guidelines in the context of increasing global uncertainty. The mechanism of the influence of hybrid challenges on the structure of financial competition of states was revealed and the need to integrate tax policy into the system of economic security was proven.Practical value. The obtained results can be used by public administration bodies to develop tax strategies aimed at increasing financial stability and ensuring financial competitiveness, forming a predictable tax environment, harmonizing national fiscal policy with international standards, as well as when developing programs for the post-war recovery of the Ukrainian economy. Key words: financial competition, tax competition, tax strategy, global uncertainty, hybrid challenges and threats, fiscal policy, financial system, economic security, BEPS, digitalization, investments, competitiveness of countries.
Keywords: financial competition; tax competition; tax strategy; global uncertainty; hybrid challenges and threats; fiscal policy; financial system; economic security; BEPS; digitalization; investments; competitiveness of countries